Global Health in Perspective: an International Mirror Class between Universidad Antonio Nariño and Universidad Continental. (VITAL, 2025)
The “Salud Global en Perspectiva” mirror class held by Universidad Antonio Nariño (Colombia) and Universidad Continental (Peru) brought together students from both institutions to analyze health systems in 12 countries, fostering critical thinking, international collaboration and intercultural communication.
Keywords: Public health; Mirror classes; Critical thinking; Health systems